Vitelline Warbler (Setophaga vitellina) songs, calls, and habitat preferences: novel acoustic descriptions of a range-restricted Caribbean songbird - Wyatt J. Cummings; David D. L. Goodman; Craig D. Layne; Katherine I. Singer; M. Whitney Thomas (PLoS ONE, 2025)
The Vitelline Warbler (Setophaga vitellina) is an understudied species endemic to a few small islands in the western Caribbean. Little is known beyond its phylogenetic relationship to other New World warblers. We used island-wide surveys and bioacoustic recordings to investigate the distribution, vocalizations, and ecology of S. vitellina across a significant portion of the species’ range on Little Cayman Island. We recorded 417 songs from 91 individuals and analyzed the length, frequency, and shape of various song components. We observed and characterized high variation in the composition and character of songs within the Little Cayman population. We also describe the call of the species and use sound files from across the species’ range to compare vocalizations between islands. Vitelline Warbler abundance is highest in dry forest and dry scrub habitats, suggesting that these habitats are most important for the species. Elaboration of the vocalizations of understudied species like the Vitelline Warbler has the potential to further our understanding of avian evolution and behavior. As much still remains to be learned from this species, action must be taken to protect its critical habitats, especially dry forests, among other conservation measures.